Comparison of the onset and offset times of two available formulations of rocuronium bromide in an animal model. Issue 1 (January 2023) - Speedy, Louise M; O'Beirn, Sean; Hopgood, Gary; Harvey, Martyn G; Cave, Grant
Rocuronium bromide is a neuromuscular blocker in widespread use in anaesthesia, emergency and intensive care. Reports of reduced efficacy of a new different formulation of rocuronium bromide were submitted to Medsafe, the New Zealand Medicines and Medical Devices Safety Authority, in 2020. Given the requirement for rapid and predictable paralysis for patient safety the efficacy of the two available formulations of rocuronium bromide was investigated in an animal model. After ethics committee approval, 19 rats were anaesthetised and paralysis, defined as loss of tibialis anterior flexion on direct electrical stimulation of the sciatic nerve, was assessed by mechanomyography in response to ED90 doses of rocuronium. Paralysis was observed at a median of 12 seconds for the new different formulation: A, Hameln Pharma (interquartile range (IQR) 6–106 seconds) and 28 seconds for formulation B: Pfizer (IQR 12–68 seconds) P = 0.48. Offset of paralysis was observed after 293 seconds for formulation A (IQR 250–372 seconds) and 241 seconds for formulation B (IQR 220–263 seconds). While the differences observed were substantial, they were not statistically significant. Moreover, the direction of observed difference was towards a shorter median onset and longer offset for the newer formulation, a finding in the opposite direction to the initial clinical concern. Relevance to the clinical situation is indeterminate given the study was stopped at low numbers for futility and limitations around the clinical applicability of animal pharmacokinetics and dynamics. Nevertheless our findings provide some reassurance that the newly available different formulation of this critical use medication does not exhibit a substantial increase in time to onset.